Kinerja Pelayanan Publik Studi Kasus Pada Dinas Kependudukan dan Catatan Sipil (Disdukcapil) Kota Jambi - Samsudin Samsudin; Ulung Pribadi (Universitas Muhammadiyah Yogyakarta, 2014)
The purpose of this study is to determine the performance of public services in the Dinas Kependudukan dan CatatanSipil Kota Jambi. This study uses the concept of performance measurement with five indicators of productivity, qualityof service, responsiveness, r esponsibility and accountability. These indica tors are used to measure the efficiency andeffectiveness of services, quality of service received by the public. The method used in this research is quantitativemethod. The research location is determined by the method of purposive, are determined by deliberate that the studywas conducted in the Depar tment of P opulation and Civil Registry. Data collection techniques used in this study includeinterviews, observations, and literature. Based on the research findings that the productivity of public services interms of the ability of officers and service performance can be summed been efficient with an average result value of70% of respondents said either. The quality of service in terms of satisfaction of the performance of services,timeliness of service, comfortable environment and good infrastructure which is an average result of 41% while themeasured responsiveness of service delivery performance , kedesiplinan, service procedur es and speed of service.The final result that stands out from the responsiveness can be judged good quality with an average of 51% of goodquality, the next responsibility is measured on the suitability of cost and fairness of service delivery is good is seenfrom the average value of responsibility is 45% and the accountability of public service in the Department of Popula-tion and Jambi City Civil Registry, is good for 70% of respondents said that responsibility.